Water-based adhesive for recycling and pressing urban waste spinning cloth into finished product
By using water-based adhesives and using acetoacetyl modified polyvinyl alcohol and other components, a high bond strength and water resistance are formed, which solves the problems of VOC emissions and high costs of isocyanate adhesives, and realizes environmentally friendly and economical adhesive applications.
Patent Information
- Application Number
- CN202411869295.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-18
- Publication Date
- 2025-03-14
AI Technical Summary
The existing isocyanate adhesives will produce VOC during production and use, which is unenvironmentally friendly and high-priced, and are not suitable for large-scale use.
An aqueous adhesive is used, including acetoacetyl modified polyvinyl alcohol, polyvinyl alcohol, non-ionic emulsifier, hydrogen peroxide, sodium acetate, tartaric acid, bisacetone acrylamide, vinyl acetate, tert-butyl hydrogen peroxide, sodium bisulfite, clay, talc, polyamide epoxychlorohydrin resin, adipic acid dihydrazide and catalyst, and the adhesive with high bonding strength and water resistance is formed through the reaction of emulsion polymerization and chemical bonding.
The aqueous adhesive has excellent bonding strength and water resistance, which reduces VOC emissions and reduces production costs, and is suitable for the recycling of pressed products of urban waste textile fabrics.
Smart Images

Figure BDA0005195351740000101
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of adhesives, and in particular relates to a water-based adhesive for recycling urban waste textile fabrics and pressing them into finished products. Background Art
[0002] In daily life and corporate production, a large amount of waste fabrics are generated. These waste fabrics are usually treated as garbage, and the simplest way to treat them is incineration, which can easily cause air pollution. Recycling and pressing waste textiles into finished products can reduce energy consumption and avoid a large amount of textile waste. At present, the recycling methods of waste fabrics are mostly direct use or more innovative and environmentally friendly recycling. The so-called recycling is to directly cut the fabric into pieces and mix it with adhesives and hot press it into boards. Generally, the adhesives used in pressing waste fabrics into artificial boards are mostly isocyanate adhesives, because isocyanates have high bonding strength and good water resistance in use, but they will produce VOCs during production and use, which is not friendly to the environment, and the price will be relatively high, which is not suitable for large-scale use.
[0003] Therefore, in view of the above shortcomings of isocyanate adhesives, there is an urgent need in the market for an adhesive that also has higher bonding strength and water resistance to replace isocyanate adhesives, and the adhesive can reduce VOC emissions. Summary of the invention
[0004] The purpose of the present invention is to provide a water-based adhesive for recycling urban waste textile fabrics into finished products, which solves the problems of poor bonding strength and water resistance in the prior art.
[0005] The purpose of the present invention can be achieved through the following technical solutions:
[0006] A water-based adhesive for recycling urban waste textile fabrics into finished products, the water-based adhesive comprising the following raw materials in parts by weight:
[0007] 1-3 parts by weight of acetoacetyl-modified polyvinyl alcohol, 1-3 parts by weight of polyvinyl alcohol, 0.1-0.2 parts by weight of nonionic emulsifier, 4-6 parts by weight of hydrogen peroxide, 0.2-0.3 parts by weight of sodium acetate, 0.6-1.2 parts by weight of tartaric acid, 0.9-1.2 parts by weight of diacetone acrylamide, 40-50 parts by weight of vinyl acetate, 0.1-0.2 parts by weight of tert-butyl hydroperoxide, 0.2-0.3 parts by weight of sodium bisulfite, 0.03-0.04 parts by weight of clay, 0.02-0.03 parts by weight of talc, 1-1.5 parts by weight of polyamide epichlorohydrin resin, 0.9-1.2 parts by weight of adipic acid dihydrazide, 1-2 parts by weight of catalyst, and 30-40 parts by weight of deionized water.
[0008] As a preferred technical solution of the present invention, the acetoacetyl-modified polyvinyl alcohol has a product number of Z-300 and is purchased from Guangdong Xinxiang International Trading Co., Ltd.
[0009] Furthermore, the acetoacetyl-modified polyvinyl alcohol of item number Z-300 has a degree of alcoholysis (mol%) of 99.0, a viscosity (mPa·s) of 26.0, a pH of 4.0, and a volatile matter (%) of 4.8.
[0010] As a preferred technical solution of the present invention, the polyvinyl alcohol model: 105, purchased from Guangzhou Xiangqian Chemical Co., Ltd.
[0011] As a preferred technical solution of the present invention, the nonionic emulsifier includes ABEX 2535.
[0012] Furthermore, the ABEX 2535 is of the brand Rhodia and was purchased from Nanjing Qinghai Trading Co., Ltd.
[0013] As a preferred technical solution of the present invention, the clay and talcum powder both have a mesh size of 800-1000.
[0014] As a preferred technical solution of the present invention, the polyamide epichlorohydrin resin has a model number of FT-DL3, which was purchased from Fengtai Environmental Protection Technology (Shandong) Co., Ltd.
[0015] As a preferred technical solution of the present invention, the catalyst includes an aluminum catalyst.
[0016] Furthermore, the aluminum catalyst includes aluminum acetylacetonate.
[0017] A method for preparing a water-based adhesive for recycling and pressing finished products of urban waste textile fabrics comprises the following steps:
[0018] S1, stirring vinyl acetate before use to obtain stirred vinyl acetate for standby use; adding distilled water to the polyamide epichlorohydrin resin to prepare solution A for standby use;
[0019] S2, take half of the weight of deionized water, add acetoacetyl-modified polyvinyl alcohol and polyvinyl alcohol, stir and dissolve at a high temperature, add non-ionic emulsifier, sodium acetate, tartaric acid and diacetone acrylamide under temperature control and stir evenly to obtain a mixture A;
[0020] S3, adding the stirred vinyl acetate to the mixture A, stirring after the addition is completed, and then adding hydrogen peroxide and the remaining deionized water in sequence, and controlling the temperature and ripening after the addition is completed to obtain a mixture B;
[0021] S4. Add tert-butyl hydroperoxide and sodium bisulfite to the mixture B under temperature control and stir, then add adipic acid dihydrazide and the catalyst under temperature control and stir evenly, add solution A and mix evenly, then add clay and talcum powder and stir again to obtain a finished water-based adhesive.
[0022] As a preferred technical solution of the present invention, the stirring before use in step S1 is stirring for 5-8 minutes 15 minutes before use; the amount of distilled water added is such that the polyamide epichlorohydrin resin is configured into a solution A with a solid content of 9-10%.
[0023] As a preferred technical solution of the present invention, the temperature increase in step S2 is to 90-95°C; the temperature of the temperature control is 70-75°C.
[0024] As a preferred technical solution of the present invention, in step S3, the method for adding the stirred vinyl acetate is to control the adding time to be 3h55min-4h05min and add dropwise while stirring; the stirring time is 30-40min; the method for adding hydrogen peroxide is to control the adding time to be 0.5h longer than the time for adding the stirred vinyl acetate and add dropwise while stirring; the temperature of the temperature-controlled aging is 75-80°C and the time is 1-1.5h.
[0025] As a preferred technical solution of the present invention, the temperature of the temperature control in step S4 is 50-60°C, and the stirring time is 30-40min; the temperature of the re-temperature control is 30-40°C; and the re-stirring time is 1-2h.
[0026] An application of a water-based adhesive for recycling and pressing urban waste textile fabrics into finished products, the application comprising: evenly mixing the water-based adhesive and fabric, placing the mixture in a mold for shaping, and subjecting the mixture to high-temperature hot pressing to obtain a waste fabric fiber board.
[0027] Beneficial effects of the present invention:
[0028] (1) The present invention uses acetoacetyl-modified polyvinyl alcohol as a protective colloid. In the initial stage of the emulsion polymerization reaction, polyvinyl alcohol will first undergo a grafting reaction with vinyl acetate to introduce acetoacetyl groups, and then introduce amide groups in the polymerization in the later stage. Due to the rich reaction properties of acetoacetyl groups and amides, the adhesive can have the ability of self-crosslinking and thermal activation, which enhances the cohesive strength of the adhesive to a certain extent. On this basis, the present invention also adds adipic acid dihydrazide and diacetone acrylamide, and a three-dimensional network structure is formed in the system, which improves the bonding ability of the adhesive. At the same time, a catalyst is also added to accelerate the rapid formation of the three-dimensional network structure of the system and increase the stability of the structure to a certain extent. Therefore, the finished adhesive obtained thereby has excellent bonding strength.
[0029] (2) The present invention compounds clay and talcum powder having a unique lamellar structure, which are stacked layer by layer in the system to form a physical barrier, thereby preventing the penetration of external water molecules and providing the system with a certain degree of water resistance. At the same time, polyamide epichlorohydrin resin is introduced to enter the lamellar gaps of clay and talcum powder through intercalation to form chemical bonds, thereby further improving the water resistance of the obtained adhesive product, so that it can maintain excellent bonding effect and stability even in a humid environment. DETAILED DESCRIPTION
[0030] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0031] The acetoacetyl-modified polyvinyl alcohol used in the embodiment of the present invention, item number: Z-300, was purchased from Guangdong Xinxiang International Trading Co., Ltd., and its alcoholysis degree (mol%): 99.0, viscosity (mPa·s): 26.0, pH: 4.0, and volatile matter (%) 4.8; the model of the polyvinyl alcohol used: 105, was purchased from Guangzhou Xiangqian Chemical Co., Ltd.; the nonionic emulsifier ABEX2535 used, its brand: Rhodia, was purchased from Nanjing Qinghai Trading Co., Ltd.; the model of the polyamide epichlorohydrin resin used: FT-DL3, was purchased from Fengtai Environmental Protection Technology (Shandong) Co., Ltd.; the above will not be repeated in the follow-up.
[0032] Example 1
[0033] A water-based adhesive for recycling urban waste textile fabrics into finished products, the water-based adhesive comprising the following raw materials in parts by weight:
[0034] 1 part by weight of acetoacetyl-modified polyvinyl alcohol, 2 parts by weight of polyvinyl alcohol, 0.1 part by weight of nonionic emulsifier, 5 parts by weight of hydrogen peroxide, 0.2 parts by weight of sodium acetate, 0.6 parts by weight of tartaric acid, 1.1 parts by weight of diacetone acrylamide, 45 parts by weight of vinyl acetate, 0.1 parts by weight of tert-butyl hydroperoxide, 0.2 parts by weight of sodium bisulfite, 0.04 parts by weight of clay, 0.025 parts by weight of talc, 1.2 parts by weight of polyamide epichlorohydrin resin, 0.9 parts by weight of adipic acid dihydrazide, 1 part by weight of catalyst, and 35 parts by weight of deionized water;
[0035] The nonionic emulsifier is ABEX 2535; the clay is 800 mesh; the talc powder is 900 mesh; and the catalyst is aluminum acetylacetonate.
[0036] A method for preparing a water-based adhesive for recycling and pressing finished products of urban waste textile fabrics comprises the following steps:
[0037] S1, stirring vinyl acetate for 5 minutes 15 minutes before use to obtain stirred vinyl acetate, which is set aside; adding distilled water to the polyamide epichlorohydrin resin to prepare a solution A with a solid content of 9%, which is set aside;
[0038] S2, take half of the above weight portion of deionized water, add acetoacetyl modified polyvinyl alcohol and polyvinyl alcohol, heat to 90 ° C and stir to dissolve, control the temperature to 72.5 ° C, add non-ionic emulsifier, sodium acetate, tartaric acid and diacetone acrylamide and stir evenly to obtain a mixture A;
[0039] S3, adding vinyl acetate dropwise to mixed material A for 3 hours and 55 minutes while stirring, stirring for 40 minutes after the addition is completed, and then adding hydrogen peroxide and the remaining deionized water in sequence, and controlling the temperature to 75° C. for 1 hour after the addition is completed to obtain mixed material B;
[0040] The hydrogen peroxide is added dropwise while stirring for 0.5 h longer than the time for adding the stirred vinyl acetate.
[0041] S4. Control the temperature of mixed material B at 55°C, add tert-butyl hydroperoxide and sodium bisulfite and stir for 30 minutes, then control the temperature for 40 minutes, add adipic acid dihydrazide and catalyst and stir evenly, add solution A and mix evenly, then add clay and talcum powder and stir for another hour to obtain the finished water-based adhesive.
[0042] Example 2
[0043] A water-based adhesive for recycling urban waste textile fabrics into finished products, the water-based adhesive comprising the following raw materials in parts by weight:
[0044] 3 parts by weight of acetoacetyl-modified polyvinyl alcohol, 1 part by weight of polyvinyl alcohol, 0.2 parts by weight of nonionic emulsifier, 4 parts by weight of hydrogen peroxide, 0.3 parts by weight of sodium acetate, 1.2 parts by weight of tartaric acid, 0.9 parts by weight of diacetone acrylamide, 50 parts by weight of vinyl acetate, 0.2 parts by weight of tert-butyl hydroperoxide, 0.25 parts by weight of sodium bisulfite, 0.035 parts by weight of clay, 0.03 parts by weight of talc, 1.5 parts by weight of polyamide epichlorohydrin resin, 1.2 parts by weight of adipic acid dihydrazide, 1.5 parts by weight of catalyst, and 30 parts by weight of deionized water;
[0045] The nonionic emulsifier is ABEX 2535; the clay is 900 mesh; the talc powder is 1000 mesh; and the catalyst is aluminum acetylacetonate.
[0046] A method for preparing a water-based adhesive for recycling and pressing finished products of urban waste textile fabrics comprises the following steps:
[0047] S1, stirring vinyl acetate for 8 minutes 15 minutes before use to obtain stirred vinyl acetate, which is set aside; adding distilled water to the polyamide epichlorohydrin resin to prepare a solution A with a solid content of 10%, which is set aside;
[0048] S2, take half of the above weight portion of deionized water, add acetoacetyl modified polyvinyl alcohol and polyvinyl alcohol, heat to 95°C and stir to dissolve, control the temperature at 70°C, add nonionic emulsifier, sodium acetate, tartaric acid and diacetone acrylamide and stir evenly to obtain a mixture A;
[0049] S3, adding vinyl acetate dropwise to mixed material A for 4 hours and 5 minutes while stirring, stirring for 30 minutes after the addition is completed, and then adding hydrogen peroxide and the remaining deionized water in sequence, and controlling the temperature to 77.5° C. for 1 hour after the addition is completed to obtain mixed material B;
[0050] The hydrogen peroxide is added dropwise while stirring for 0.5 h longer than the time for adding the stirred vinyl acetate.
[0051] S4. Control the temperature of mixed material B at 50°C, add tert-butyl hydroperoxide and sodium bisulfite and stir for 40 minutes, then control the temperature for 30 minutes, add adipic acid dihydrazide and catalyst and stir evenly, add solution A and mix evenly, then add clay and talcum powder and stir for 2 hours to obtain the finished water-based adhesive.
[0052] Example 3
[0053] A water-based adhesive for recycling urban waste textile fabrics into finished products, the water-based adhesive comprising the following raw materials in parts by weight:
[0054] 2 parts by weight of acetoacetyl-modified polyvinyl alcohol, 3 parts by weight of polyvinyl alcohol, 0.15 parts by weight of nonionic emulsifier, 6 parts by weight of hydrogen peroxide, 0.25 parts by weight of sodium acetate, 0.9 parts by weight of tartaric acid, 1.2 parts by weight of diacetone acrylamide, 40 parts by weight of vinyl acetate, 0.15 parts by weight of tert-butyl hydroperoxide, 0.3 parts by weight of sodium bisulfite, 0.03 parts by weight of clay, 0.02 parts by weight of talc, 1 part by weight of polyamide epichlorohydrin resin, 1 part by weight of adipic acid dihydrazide, 2 parts by weight of catalyst, and 40 parts by weight of deionized water;
[0055] The nonionic emulsifier is ABEX 2535; the clay is 1000 mesh; the talc powder is 800 mesh; and the catalyst is aluminum acetylacetonate.
[0056] A method for preparing a water-based adhesive for recycling and pressing finished products of urban waste textile fabrics comprises the following steps:
[0057] S1, stirring vinyl acetate for 6.5 minutes 15 minutes before use to obtain stirred vinyl acetate, which is set aside; adding distilled water to the polyamide epichlorohydrin resin to prepare a solution A with a solid content of 9%, which is set aside;
[0058] S2, take half of the above weight portion of deionized water, add acetoacetyl modified polyvinyl alcohol and polyvinyl alcohol, heat to 92.5 ° C and stir to dissolve, control the temperature to 75 ° C, add non-ionic emulsifier, sodium acetate, tartaric acid and diacetone acrylamide and stir evenly to obtain a mixture A;
[0059] S3, adding vinyl acetate dropwise to mixed material A for 4 hours while stirring, stirring for 35 minutes after the addition is completed, and then adding hydrogen peroxide and the remaining deionized water in sequence, and controlling the temperature to 80° C. for 1.5 hours after the addition is completed to obtain mixed material B;
[0060] The hydrogen peroxide is added dropwise while stirring for 0.5 h longer than the time for adding the stirred vinyl acetate.
[0061] S4. Control the temperature of mixed material B at 60°C, add tert-butyl hydroperoxide and sodium bisulfite, and stir for 35 minutes. Control the temperature for another 35 minutes, add adipic acid dihydrazide and the catalyst, and stir evenly. Add solution A, mix evenly, add clay and talcum powder, and stir for another 1.5 hours to obtain the finished water-based adhesive.
[0062] Comparative Example 1
[0063] Compared with Example 3, the difference is that in Comparative Example 1, acetoacetyl-modified polyvinyl alcohol is not added, and the other operating steps and parameters remain unchanged.
[0064] Comparative Example 2
[0065] Compared with Example 3, the difference is that adipic acid dihydrazide is not added in Comparative Example 2, and the other operating steps and parameters remain unchanged.
[0066] Comparative Example 3
[0067] Compared with Example 3, the difference is that diacetone acrylamide is not added in Comparative Example 3, and the other operating steps and parameters remain unchanged.
[0068] Comparative Example 4
[0069] Compared with Example 3, the difference is that no catalyst is added in Comparative Example 4, and the other operating steps and parameters remain unchanged.
[0070] Comparative Example 5
[0071] Compared with Example 3, the difference is that in Comparative Example 5, no clay is added, and talcum powder of equal weight is used instead, and the other operating steps and parameters remain unchanged.
[0072] Comparative Example 6
[0073] Compared with Example 3, the difference is that talcum powder is not added in Comparative Example 6, and clay of equal weight is used instead, and the other operating steps and parameters remain unchanged.
[0074] Comparative Example 7
[0075] Compared with Example 3, the difference is that in Comparative Example 7, no polyamide epichlorohydrin resin is added, and the other operating steps and parameters remain unchanged.
[0076] Performance Testing
[0077] (1) Formaldehyde content detection: According to GB / 18583-2008, the free formaldehyde content of the adhesive products prepared in Examples 1-3 and Comparative Examples 1-7 was detected using a spectrophotometer. The results are shown in Table 1.
[0078] (2) Viscosity test: According to GB / T 11175-2002, the viscosity of the adhesive products prepared in Examples 1-3 and Comparative Examples 1-4 was measured. The results are shown in Table 1.
[0079] (3) Bond strength measurement: Take a group (2) of wooden pieces of the same specifications and apply 100 g / cm2 of adhesive strength to the corresponding contact surface of each wooden piece. 2 The adhesive products prepared in Examples 1-3 and Comparative Examples 1-4 were respectively coated, and the specification of each contact surface was 90 mm*5 mm. Then, the contact surfaces of the two wooden pieces were overlapped and pressed, and a pressure of 1 MPa was applied to the contact surfaces. After being placed at room temperature for 24 hours, a tensile shear test was performed, and the average value was taken after repeating 5 times. The results are shown in Table 1.
[0080] (4) Water resistance test: Take a group of wood block samples with the same specifications, length: 150mm; width: 20mm; thickness: 5mm, and press 150g / cm on the contact surface of each sample. 2 The finished adhesives prepared in Examples 1-3 and Comparative Examples 5-7 were applied respectively, and then the contact surfaces of the two wooden pieces were pressed together, and a pressure of 1 MP was applied to the contact surfaces. The bonded samples were placed at room temperature for seven days, and then soaked in cold water (temperature the same as room temperature) for four days. The strength of the samples was tested with a tensile machine, and the results are shown in Table 1.
[0081] (5) Determination of film moisture content: Weigh 0.3 g of the finished adhesives prepared in Examples 1-3 and Comparative Examples 5-7 respectively in a watch glass, wait for them to dry naturally to form a film, weigh the mass of the dry film, soak it in clean water at room temperature for 24 h, take it out and put it in a 55°C oven to dry for 24 h, weigh the mass of the dry film, and calculate the film moisture content according to the following formula:
[0082] Moisture-free rate (%) = mass of dried film after soaking in water / mass of naturally dried film × 100%;
[0083] The results are shown in Table 1.
[0084] Table 1
[0085]
[0086] It can be seen from Table 1 that the adhesive product prepared by the present invention has excellent bonding strength and water resistance and does not contain formaldehyde.
[0087] In the description of the specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.
[0088] The above contents are merely examples and explanations of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the invention or exceed the scope defined by the claims, they shall all fall within the protection scope of the present invention.
Claims
1. A water-based adhesive for recycling and pressing urban waste textile fabrics into finished products, characterized in that: The water-based adhesive comprises the following raw materials in parts by weight: 1-3 parts by weight of acetoacetyl-modified polyvinyl alcohol, 1-3 parts by weight of polyvinyl alcohol, 0.1-0.2 parts by weight of nonionic emulsifier, 4-6 parts by weight of hydrogen peroxide, 0.2-0.3 parts by weight of sodium acetate, 0.6-1.2 parts by weight of tartaric acid, 0.9-1.2 parts by weight of diacetone acrylamide, 40-50 parts by weight of vinyl acetate, 0.1-0.2 parts by weight of tert-butyl hydroperoxide, 0.2-0.3 parts by weight of sodium bisulfite, 0.03-0.04 parts by weight of clay, 0.02-0.03 parts by weight of talc, 1-1.5 parts by weight of polyamide epichlorohydrin resin, 0.9-1.2 parts by weight of adipic acid dihydrazide, 1-2 parts by weight of catalyst, and 30-40 parts by weight of deionized water.
2. The aqueous adhesive for recycling and pressing urban waste textile fabrics into finished products according to claim 1, characterized in that: The nonionic emulsifier includes ABEX 2535.
3. The aqueous adhesive for recycling and pressing urban waste textile fabrics into finished products according to claim 1, characterized in that: The clay and talc both have a mesh size of 800-1000.
4. The aqueous adhesive for recycling and pressing urban waste textile fabrics into finished products according to claim 1, characterized in that: The catalyst includes an aluminum catalyst.
5. The aqueous adhesive for recycling and pressing urban waste textile fabrics into finished products according to claim 4, characterized in that: The aluminum catalyst includes aluminum acetylacetonate.
6. A method for preparing a water-based adhesive for recycling and pressing finished products of urban waste textile fabrics as claimed in any one of claims 1 to 5, characterized in that: The steps include: S1, stirring vinyl acetate before use to obtain stirred vinyl acetate for standby use; adding distilled water to the polyamide epichlorohydrin resin to prepare solution A for standby use; S2, take half of the weight of deionized water, add acetoacetyl-modified polyvinyl alcohol and polyvinyl alcohol, stir and dissolve at a high temperature, add non-ionic emulsifier, sodium acetate, tartaric acid and diacetone acrylamide under temperature control and stir evenly to obtain a mixture A; S3, adding the stirred vinyl acetate to the mixture A, stirring after the addition is completed, and then adding hydrogen peroxide and the remaining deionized water in sequence, and controlling the temperature and ripening after the addition is completed to obtain a mixture B; S4. Add tert-butyl hydroperoxide and sodium bisulfite to the mixture B under temperature control and stir, then add adipic acid dihydrazide and the catalyst under temperature control and stir evenly, add solution A and mix evenly, then add clay and talcum powder and stir again to obtain a finished water-based adhesive.
7. The method for preparing a water-based adhesive for recycling and pressing finished products of urban waste textile fabrics according to claim 6, characterized in that: The stirring before use in step S1 is 15 minutes before use and then 5-8 minutes; the amount of distilled water added is such that the polyamide epichlorohydrin resin is configured into a solution A with a solid content of 9-10%.
8. The method for preparing a water-based adhesive for recycling and pressing finished products of urban waste textile fabrics according to claim 6, characterized in that: The temperature in step S2 is raised to 90-95°C; the temperature of the temperature control is 70-75°C.
9. The method for preparing a water-based adhesive for recycling and pressing finished products of urban waste textile fabrics according to claim 6, characterized in that: In step S3, the method for adding the stirred vinyl acetate is to control the adding time to be 3h55min-4h05min and add it dropwise while stirring; the stirring time is 30-40min; the method for adding hydrogen peroxide is to control the adding time to be 0.5h longer than the time for adding the stirred vinyl acetate and add it dropwise while stirring; the temperature of the temperature-controlled aging is 75-80°C and the time is 1-1.5h.
10. The method for preparing a water-based adhesive for recycling and pressing finished products of urban waste textile fabrics according to claim 6, characterized in that: In step S4, the temperature of the temperature control is 50-60°C, and the stirring time is 30-40min; the temperature of the re-temperature control is 30-40°C; and the re-stirring time is 1-2h.